Resolvin D1 Reduces Lung Infection and Inflammation Activating Resolution in Cystic Fibrosis - Isopi, Elisa; Mattoscio, Domenico; Codagnone, Marilina; Mari, Veronica Cecilia; Lamolinara, Alessia; Patruno, Sara; D’Aurora, Marco; Cianci, Eleonora; Nespoli, Annalisa; Franchi, Sara; Gatta, Valentina; Dubourdeau, Marc; et al. (Frontiers in Immunology, 2020)
Non-resolving lung inflammation and P. aeruginosa infections are the underlying cause of morbidity and mortality in cystic fibrosis (CF). The endogenous lipid mediator resolvin (Rv) D1 is a potent regulator of resolution and its roles, actions, and therapeutic potential in CF are of interest. Here we investigated actions and efficacy of RvD1 in preclinical models of cystic fibrosis. Cftr knockout mice with chronic P. aeruginosa lung infection were treated with RvD1 to assess differences in lung bacterial load, inflammation, and tissue damage. Cells from volunteers with CF were treated with RvD1 during ex vivo infection with P. aeruginosa and effects on phagocytosis and inflammatory signaling were determined. In CF mice, RvD1 reduced bacterial burden, neutrophil infiltration, and histological signs of lung pathology, improving clinical scores of diseases. Mechanistically, RvD1 increased macrophage-mediated bacterial and leukocyte clearance in vivo. The clinical significance of these findings is supported by actions in primary leukocytes and epithelial cells from volunteers with CF where RvD1 enhanced P. aeruginosa phagocytosis and reduced genes and proteins associated to NF-κB activation and leukocyte infiltration. Concentration of RvD1 in sputum from patients with CF was also inversely correlated to those of cytokines and chemokines involved in CF lung pathology. These findings demonstrate efficacy of RvD1 in enhancing resolution of lung inflammation and infections and provide proof of concept for its potential as a prototypic novel pro-resolutive therapeutic approach for CF.